2022
DOI: 10.1155/2022/5240046
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin Protein In Situ Expression Predicts Less Tumor Metastasis and Overall Better Survival of Endometrial Carcinoma

Abstract: Background. Vimentin, a cytoplasmic intermediate filament protein, has been recently identified to be a prognostic biomarker in some cancers. However, the function of vimentin in endometrial carcinoma (EC) remains unclear. Our study aimed at evaluating vimentin expression in EC and preliminarily exploring the role of vimentin in EC progression. Methods. In total, 341 EC patients who underwent surgical follow-up were enrolled in the retrospective study. Vimentin expression levels in EC tissues were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Our data clearly shows that loss of vimentin expression is highly prognostic in the subset of patients with FIGO I tumors as well as in endometrioid patients and in the full cohort. Our data is in line with previous reports 51 , 52 describing an association between loss of vimentin expression and non-endometrioid tumors, higher FIGO stage, higher tumor grade and worse patient outcome and we here add important information on vimentin in low-stage tumors. Our data also indicate that the cut-off for detecting low expression of vimentin is broad, as both loss and low expression (lowest quartile) predict poor prognosis, further supporting the robustness of this marker to identify patients at risk of recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…Our data clearly shows that loss of vimentin expression is highly prognostic in the subset of patients with FIGO I tumors as well as in endometrioid patients and in the full cohort. Our data is in line with previous reports 51 , 52 describing an association between loss of vimentin expression and non-endometrioid tumors, higher FIGO stage, higher tumor grade and worse patient outcome and we here add important information on vimentin in low-stage tumors. Our data also indicate that the cut-off for detecting low expression of vimentin is broad, as both loss and low expression (lowest quartile) predict poor prognosis, further supporting the robustness of this marker to identify patients at risk of recurrence.…”
Section: Discussionsupporting
confidence: 92%
“…To further clarify the possible molecular mechanism by which PPP1R14B promotes tumour development, GO analysis, KEGG analysis, and GSEA were performed. The results showed that PPP1R14B was negatively associated with intermediate filament‐related pathways, and intermediate filaments could inhibit UCEC metastasis and invasion 51,52 . In addition, hormone activity and oestrogen signalling pathways were found to be enriched.…”
Section: Discussionmentioning
confidence: 97%
“…The results showed that PPP1R14B was negatively associated with intermediate filamentrelated pathways, and intermediate filaments could inhibit UCEC metastasis and invasion. 51,52 In addition, hormone activity and oestrogen signalling pathways were found to be enriched. Given that endometrial cancer formation is associated with dysplasia caused by oestrogen overstimulation, this result suggests that involvement in this process may also be one of the mechanisms by which PPP1R14B promotes endometrial cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in certain malignancies such as endometrial cancer, the lack of vimentin expression has been correlated significantly with lymph node metastasis, deep myometrium invasion, lymph vascular space invasion, advanced stages (III and IV), and higher tumor grade. Indeed, vimentin-negative patients had poorer overall survival compared with vimentin-positive patients [38]. Additionally, it has also been described an interesting participation of vimentin against certain viral infections [37].…”
Section: Discussionmentioning
confidence: 99%